Oral health knowledge among parents of autistic child in Bandung-Indonesia - Yetty Herdiyati Nonong; Arlette Setiawan; Fellani Danasra Dewi; Cugati Navaneetha (Dental Journal (Majalah Kedokteran Gigi), 2014)
Background: Autistic children as well as other special needs individual demand special care given by their parents. But there exist limited awareness among parents in Indonesia society, especially with regard to their oral health. Purpose: The study was aimed to assess the oral health related knowledge, attitude and behavior of the parents; and oral health status of their autistic children in comparison with non-autistic children. Methods: Total of 56 children (23 autistic and 23 normal) between 7-12 years was included in this study. Data on parents’ knowledge, attitude, oral health practice and behavior of their children were gathered from the questionnaires. The oral health status of the children was recorded using deft and DMFT caries index. Results: All obtained data were analyzed using sPss version 13 to correlate the index of the sample. It showed that caries index of autistic child was lower and limited oral health knowledge among parents. Conclusion: There is need of greater awareness to be spread among the population of Indonesia about the existing professional help for the special children and educate the parents to maintain their child’s oral health for a better quality of life.Latar belakang: Anak autis seperti juga individu berkebutuhan khusus lainnya memerlukan perhatian khusus dari orang tuanya. Namun banyak keterbatasan kesadaran orang tua dalam masyarakat Indonesia, terutama berkaitan dengan kesehatan mulut anak autis mereka. Tujuan: Penelitian ini bertujuan untuk menguji pengetahuan kesehatan gigi, perilaku orang tua dan anak mereka yang autis. Metode: Data pengetahuan orang tua dikumpulkan dari kuesioner dan status kesehatan mulut anak dicatat menggunakan indeks karies DMFT dan deft. sejumlah 56 anak (23 autis dan 23 non-autis sebagai kelompok kontrol) usia 7-12 tahun ikut serta dalam penelitian ini. Hasil: Data yang didapatkan dianalisis menggunakan sPss versi 13 untuk mengkorelasikan indeks subjek. Hasil menunjukkan indeks karies anak autis lebih rendah dengan pengetahuan kesehatan mulut orang tua yang terbatas. Simpulan: Diperlukan penyebarluasan kesadaran yang lebih tinggi di antara populasi orang Indonesia mengenai mempertahankan status kesehatan mulut anak autis mereka untuk mencapai kualitas hidup yang lebih baik.